CUSTOMER SATISFACTION LEMBAGA-LEMBAGA DAKWAH - Jauhari, Tontowi (BINA' AL-UMMAH, 2016)
This study aims to understand the influence of public services (transparency, reliable, responsive, fair and empathy) on customer satisfaction (satisfactory experience, faithful service, and risk services) in the institutions of da'wah (KBIH, LAS, and KUA) in Banadar Lampung. The study sample were 45 respondents taken using a sampling technique of probability sampling (random sampling) based on clusters. The study uses a qualitative- quantitative approach and survey method and regression analysis. The results show that the public service customer has effect on customer satisfaction of institutions of propaganda in Bandar Lampung. Findings show the need to improve the handling and improvement in providing services in tersm of; transparency, reliability, responsiveness, fairness, and empathy. There fore, the users of dakwah institution will be more satisfied in the future.